Origin, norms, and the motherhood penalty - Olof Åslund; Arizo Karimi; Anton Sundberg (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2025)
We present evidence that shared institutional and economic contexts may be at least as important as culturally rooted gender equality norms for the size of the motherhood penalty. Our study covers child migrants and children of immigrants in Sweden, and while the results point to a moderate but statistically robust negative association between source country gender equality and the labor market impact of motherhood, the overall picture is more one of similarity across highly diverse groups. All groups of mothers exhibit qualitatively comparable labor market trajectories following first childbirth, but penalties are somewhat greater among those descending from the most gender unequal societies.
Keywords: 330; Mütter; Soziale Werte; Migranten; Arbeitsangebot; Erwerbstätigkeit; Lohn; Schweden